2013
DOI: 10.1177/1356336x13508684
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in pupils’ assessments of physical education lessons in regard to their self-perception of physical fitness across the educational systems of Czech Republic and Poland

Abstract: Observation of trends in physical education plays an integral role in motor-development diagnostics and in encouraging physical activity and a healthy lifestyle. This study aims to elucidate the current state of and trends in pupils' assessments of physical education lessons (PELs) in different education systems in the context of self-perception of physical fitness. The research was conducted during PELs taught by student teachers at primary schools and high schools in the Czech Republic and in Poland. Schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…As children age, rates of overweight and obesity rise (2), cardiovascular fitness declines (3), incorrect body posture increases (4), and mental health disorders increase, especially among girls (5). There is also a decline in physical activity (PA) as children age (6,7), particularly for intense PA (8), along with decreasing interest in physical education (PE) (9). Indeed, by 2012, only 35 of 131 European studies reported that adolescents met daily PA recommendations (10) and in Central-Eastern European countries, high levels of sedentary behaviors have been recorded (11).…”
Section: Introductionmentioning
confidence: 99%
“…As children age, rates of overweight and obesity rise (2), cardiovascular fitness declines (3), incorrect body posture increases (4), and mental health disorders increase, especially among girls (5). There is also a decline in physical activity (PA) as children age (6,7), particularly for intense PA (8), along with decreasing interest in physical education (PE) (9). Indeed, by 2012, only 35 of 131 European studies reported that adolescents met daily PA recommendations (10) and in Central-Eastern European countries, high levels of sedentary behaviors have been recorded (11).…”
Section: Introductionmentioning
confidence: 99%
“…Student attitude toward PE and physical activity is often researched with qualitative and quantitative tools with various properties of reliability and validity (Silverman & Subramaniam, 1999). In our submission, we utilize statements of pupils recorded using a standardized questionnaire developed 20 years ago and since then widely used in PE research (Frömel, El Ansari, & Vašíčková, 2009;Frömel, Vasendova, & Krapkova, 2000;Frömel, Vasendova, Stratton, & Pangrazi, 2002;Frömel, et al, 2014;Chmelík, Frömel, Svozil, & Maleňáková, 2007;Sigmund, Sigmundová, Frömel, & Vašíčková, 2010). Investigation using a standardized questionnaire brings important information not only to the researchers but also to the broader professional community (Frömel, Novosad, & Svozil, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Completing the questionnaire took 5 minutes and pupils apart from basic information stated their preferences of PE lesson by answering YES-NO simple question "Is Physical Education your favourite subject?". The questionnaire then comprised of 24 questions (maximum is 24 points) that are divided into six dimensions (4 question forms each dimension, maximum is 4 points) and one additional dimension (8 selected questions, maximum is 8 points) (Frömel, et al, 2014). Positive answers are often expressed in percentage (or in mean values) and demonstrate the attitude of a pupil toward a finished PE lesson.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid decreases in physical activity (PA) occur during adolescence [5][6][7][8] and continue later, in adulthood [9,10]. Similarly, there is a decline in level of vigorous PA [11,12] and growing lack of interest in physical education lessons in adolescence [13]. Boys have been shown to be more physically active than girls during both school and weekend days [14][15][16], while adolescents of both genders are less physically active on weekends than on school days [17][18][19].…”
Section: Introductionmentioning
confidence: 99%